PENGEMBANGAN E-MODUL PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING PADA MATA PELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Dhara Atika Putri; Nanik Setiawati; Fentia Afrida (Jurnal Tunas Pendidikan, 2026)
This research is motivated by the problem of learning Natural and Social Sciences (IPAS) in class IV SDN 20 Sitiung which is still monotonous, less contextual, and limited to the use of printed modules from the government. Based on interviews with class teachers and the results of curriculum analysis, it was found that IPAS learning has not linked the material to students' real lives and has not utilized the available digital facilities optimally. The purpose of this study is to develop an E-Module based on Problem Based Learning (PBL) that can improve student engagement and learning outcomes. This study uses the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). Data were collected through observation, interviews, questionnaires, tests, and documentation, then analyzed with validity, practicality, and effectiveness tests. The development results showed that the E-Module designed using the Flipbook Maker application was very valid with a content expert score of 94.3% and a language expert score of 83.4%. The practicality test showed a score of 97.3% by teachers and 100% by students. From the effectiveness test, 89% of students achieved learning completion. This E-Module is also able to increase students' interest in learning and encourage contextual problem-solving activities. Thus, the development of PBL-based E-Module is effective in improving the quality of science learning in elementary schools.